The Prevention of Child Marriage Through The Women’s School To Improve Quality of Life (Sekoper PKH) In Mengen Village, Bondowoso Regency - Zuhri Ernada, Sus Eko; Dody Molasy, Honest; Dwi Eriyanti, Linda; Nur Budiman, Bachtiar; Dewi Safitri, Bella (Green Publisher Indonesia, 2022)
Child marriage is one of the serious problems faced by Bondowoso Regency. As a district with the lowest economic level and high child marriage rates, the quality of life and generations in Bondowoso Regency are threatened and vulnerable because of socio-economic problems such as poverty and high divorce rates, health problems such as increased maternal and child mortality, increased stunting rates, and malnutrition. One of the villages in Bondowoso which has problems with child marriage is Mengen Village. To overcome these problems, the Department of Social Affairs of Bondowoso which focused on the empowerment of women and protection for children (P3AKB) launched the Women's School program to improve the quality of life or Sekolah Perempuan Peningkatan Kualitas Hidup (SEKOPER PKH) which aims to improve the quality of PKH (Program Keluarga Harapan, Government Incentive Program) beneficiaries. SEKOPER PKH has been up and running since 2018 and focuses on household financial management. The presence of a community development grant scheme by the Institute for Research and Community Service (LP2M) University of Jember can help solve the problem of child marriage in Bondowoso. The approach used to solve this is the grounded method with the Focus Group Discussion (FGD) method to collect data and evidence as the basis for preparing textbooks and modules. After the module and reference book has been published, the team will conduct Training of Trainers (ToT) to improve the ability of teaching for voluntary teachers. When the voluntary teachers have the ability to teach and implement the teaching module properly, the module will be implemented to the PKH beneficiaries.